2014
DOI: 10.3121/cmr.2014.1245
|View full text |Cite
|
Sign up to set email alerts
|

Survival Comparisons for Breast Conserving Surgery and Mastectomy Revisited: Community Experience and the Role of Radiation Therapy

Abstract: Objectives: Evidence suggests superiority of breast conserving surgery (BCS) plus radiation over mastectomy alone for treatment of early stage breast cancer. Whether the superiority of BCS plus radiation is related to the surgical approach itself or to the addition of adjuvant radiation therapy following BCS remains unclear. Materials and Methods:We conducted a retrospective cohort study of women with breast cancer diagnosed from 1994-2012. Data regarding patient and tumor characteristics and treatment specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 37 publications
(58 reference statements)
7
70
0
4
Order By: Relevance
“…Our results further support the hypothesis that BCT might be the preferred choice for breast cancer patients when both BCT and mastectomy are suitable treatment options . A previous observational study that also investigated survival outcomes following both types of surgery hypothesized that the prognostic advantage of BCT over mastectomy may be related to the effects of RT as a component of BCT while early stage mastectomy patients in general receive no RT5.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results further support the hypothesis that BCT might be the preferred choice for breast cancer patients when both BCT and mastectomy are suitable treatment options . A previous observational study that also investigated survival outcomes following both types of surgery hypothesized that the prognostic advantage of BCT over mastectomy may be related to the effects of RT as a component of BCT while early stage mastectomy patients in general receive no RT5.…”
Section: Discussionsupporting
confidence: 84%
“…A possible explanation for the differences in BCSS between the two time cohorts, apart from the difference in the applied chemotherapy regimens, is the length of follow‐up. Recurrence peaks (including local/locoregional recurrences and distant metastases) are described to occur 2, 5 and 9 years after diagnosis . Since the 2006–2012 cohort had a median follow‐up of 7 years, this cohort may have had too short follow‐up to reveal the effect of BCT and mastectomy after 7 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast conserving surgery (BCS), followed by adjuvant radiation therapy (RT), is an essential arm in the treatment management of women with early-stage breast cancer 2. Onitilo et al3 demonstrated that the judicious use of adjuvant RT post-BCS improves survival outcomes compared to radical mastectomy alone 3. Adjuvant RT also halves the recurrence rate thereby significantly improving survival rates 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…Although how much this extends into clinical and long term survival benefit is still a matter of debate. Clinical trials exist for both invasive and in situ carcinoma in which no significant difference in survival was found in patients treated with BCT or mastectomy [24][25][26]. Both radiation therapy and adjuvant systemic chemotherapy contribute to low rates of cancer recurrence in treated breast.…”
Section: Detection Of Additional Lesions On Mri With or Without Non Mmentioning
confidence: 99%